2016
DOI: 10.1139/cjas-2016-0020
|View full text |Cite
|
Sign up to set email alerts
|

Dietary regulation of Ucp2 and Ucp3 expressions in white adipose tissues of beef cattle

Abstract: Expression of uncoupling protein (Ucp) 2 but not Ucp3 in subcutaneous fat was significantly higher in cattle fed the concentrate diet than in those fed the roughage diet. Ucp2 expression in mesenteric fat was higher in cattle fed the vitamin A-deficient diet than in those fed the control diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
2
1
Order By: Relevance
“…Since the regulation of gene transcription is generally cell‐type dependent, the present results are likely in part, a reflection of the regulation of Ucp1 in myogenic cells. In fact, we previously showed that diet‐related changes in Ucp1 expression were closely related to those in Ucp2 expression in bovine fat 25,33,41 . In the current study, we found no similar changes between Ucp1 expression and Ucp2 expression in response to A‐83‐01 and LDN‐193189 treatments in myogenic cells.…”
Section: Resultscontrasting
confidence: 84%
See 1 more Smart Citation
“…Since the regulation of gene transcription is generally cell‐type dependent, the present results are likely in part, a reflection of the regulation of Ucp1 in myogenic cells. In fact, we previously showed that diet‐related changes in Ucp1 expression were closely related to those in Ucp2 expression in bovine fat 25,33,41 . In the current study, we found no similar changes between Ucp1 expression and Ucp2 expression in response to A‐83‐01 and LDN‐193189 treatments in myogenic cells.…”
Section: Resultscontrasting
confidence: 84%
“…We previously showed a close relationship between Ucp1 expression and Ucp2 expression in bovine fat 33 . PPARγ stimulates transcription of murine Ucp1 and Ucp2 34,35 .…”
Section: Resultsmentioning
confidence: 90%
“…The UCP2 gene is almost ubiquitously expressed throughout body tissues [49]. It is regulated by TR and PPARγ and was recently shown to be regulated by diet in subcutaneous white adipose tissue of cattle [50]. However, our heifers had been offered the same diet for 6 mo before PREG biopsises were taken.…”
Section: Resultsmentioning
confidence: 99%